Pengelolaan Sumberdaya Alam Pantai Batu Pinagut - Botutihe, Nur Meyla Ulfiana (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2024)
The research was carried out in Boroko Village, North Bolang Mongodow Regency with the aims of: (1) collecting data on natural resources on the Batu Pinagut coastline (2) Describing the potential for developing natural resources on the Batu Pinagut coastline (3) Analyzing policies on damage control. Determination of the sample using purposive sampling technique. Data was collected using observation, interview, documentation and document recording techniques. The results of the research show: (1) Batu Pinagut Beach has coastal resource potential that has been developed, namely biological resources and non-biological resources (2) management of coastal resources in Pemuteran Village includes tourism coral reef conservation in terms of tourism service training (3) Resource policy needs regulations are enforced, so that there is balance, preservation and continuity of resources. The rules do not apply to all areas, but to areas needed for the spawning and breeding of marine biota. To manage this area, it is necessary to have a conservation area that is equally understood and recognized by every stakeholder, stakeholders, fishermen, government, community and government. The rules and policies that are implemented involve stakeholders which become a culture that develops in society so that protection/conservation areas become a necessity and are implemented consciously by the community Keywords: Batu Pinagut Beach, Coastal Natural Resources